A better way to assess and document for patients presenting to A&E with Craniomaxillofacial Trauma through the implementation of a standardised proforma. Issue 1 (January 2022) - Howells, Ryan
Abstract : Introduction: Comprehensive and methodical assessment of a trauma patient, with clear, concise documentation is essential for effective triage, and management of their injuries. Assessing a patient with maxillofacial trauma can be overwhelming, and stressful environments lead to omissions and errors. The utility and efficacy of checklists and proformas is well-established, with notable examples such as the WHO surgical safety checklist becoming mandatory. Aims: * Undertake a service improvement project and produce a proforma for use in assessment and documentation of maxillofacial trauma patients. * Demonstrate improved clinical data collection, documentation and communication in accordance with clinical governance. Methods: * Initial focus groups with DCTs, StRs and Consultants to highlight areas for improvement. * Literature review and discussion to establish desirable clinical records and create proforma document accordingly. * Comparative analysis of clinical documentation pre and post-proforma, followed by proforma revision and reassessment as needed. * Follow-up focus group to assess impact on communication and clinician satisfaction. Results: The initial audit of 49 records demonstrated significant heterogeneity in assessment and documentation with over 80% lacking key data points. Following implementation of a standardised proforma the standard of assessment and record keeping as defined by this study improved to greater than 90% on reaudit of 42 records. Conclusions: The author believes this OMFS trauma proforma helps to guide and structure clinical assessment for junior and senior colleagues alike, and reduces errors of omission. This standardised approach relieves the cognitive burden during busy on-calls and promotes comprehensive documentation and improved communication within OMFS teams by providing a ready-made and consistent medico-legal document.